2016
DOI: 10.1186/s12891-016-0978-y
|View full text |Cite
|
Sign up to set email alerts
|

Healing of rotator cuff tendons using botulinum toxin A and immobilization in a rat model

Abstract: BackgroundWe evaluated effects of botulinum toxin A (Botox) and cast immobilization on tendon healing in a rat model. Injection of Botox into rat supraspinatus was hypothesized to reduce muscle active force and improved healing.MethodsEighty-four supraspinatus tendons were surgically transected and repaired in 42 Sprague-Dawley rats (transosseous technique). After repair, supraspinatus muscle was injected with saline or Botox (3 or 6 U/kg). Half the shoulders were cast-immobilized for the entire postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Several studies have reported pain relief following Botox injection after achieving sufficient suppression of muscular function in lateral epicondylitis [ 14 , 22 ]. A potential mechanism of improved tendon function was reported in an animal study where Botox was injected into the supraspinatus muscle for repair of rotator cuff injury showing an improvement of collagen fibres alignment at the tendon-bone interface [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported pain relief following Botox injection after achieving sufficient suppression of muscular function in lateral epicondylitis [ 14 , 22 ]. A potential mechanism of improved tendon function was reported in an animal study where Botox was injected into the supraspinatus muscle for repair of rotator cuff injury showing an improvement of collagen fibres alignment at the tendon-bone interface [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Col I, essential for fibrous tissues repair and regeneration, is one the main ECM protein in tendon [19]. The collagen fibers longitudinal arrangement is important to provide mechanical properties of tendons and can maintain the physiological structure [20, 21]. The rat model showed that the control group had more Col I and Col III accumulation in the wound area.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical stability and the local mechanical environment are required for optimal repair of injured tissues for both tendon and bone [14,16,7476]. While complete immobilization is not ideal for either tendon or bone repair [4,75,7780], too much loading can lead to failed repair, gapping (in tendon) and non-unions (in bone) [8184]. There exists a range of therapeutic loading that promotes tissue regeneration while allowing for sufficient healing processes [85,86].…”
Section: Intact Tendon Maintains Mechanical Stability Of Healing Bonementioning
confidence: 99%